Investigation of properties of lubricants in locomotive diesels - Bučinskas, Vytautas; Mokšin, Vadim; Subačius, Rimantas (Transport, 2004)
This paper describes experimental investigation of lubricant properties used in locomotive engines. The workbench for experimental investigation is described, which presented theoretical background and technique of the experiment. The results are analyzed and presented graphically. Their interpretation shows the direction for further investigation. Final conclusions of the results are made.First Published Online: 27 Oct 2010